MORPHOMETRICS OF FULVOUS FRUIT BAT (ROUSETTUS LESCHENAULTI) FROM LAHORE, PAKISTAN - M. Shahbaz; A. Javid; T. Javed; M. Mahmood-ul-Hassan; S.M. Hussain (Journal of Animal and Plant Sciences, 2014)
Present study on Fulvous fruit bat (Rousettus leschenaulti) from October 2011 to March 2012 in the vicinity of Lahore, Pakistan took morphometric measurements of 15 (9♂ and 6♀) bat specimens. The average head and body length of all 15 specimens was 99.55 ± 15.035mm, forearm was 77.64 ± 6.373mm long, lengths of 3rd, 4th and 5th metacarpals were 52.73 ± 4.832 mm, 51.56 ± 4.996mm and 49.86 ± 3.998, respectively and the tail length was 11.1 ± 3.072mm. The greatest skull length (n= 9) was 35.89 ± 2.848mm, breadth of braincase was 15.44 ± 1.509mm while bacular length of a male specimen was 3.075mm.
Keywords: Fulvous fruit bat; Greatest skull length; Baculum; Badian